PROPOSTA DE METODOLOGIA PARA REALIZAÇÃO DE AUDITORIA DE SISTEMAS DE GESTÃO DA QUALIDADE - Rebelo, Antonio Raimundo Coutinho (2008)
This work introduces an improvement proposal to the most updated methodology used on the management system audits applied to quality discipline. The standard ISO 19011:2002 constitutes the base for all process of management system audit. This proposal has as focus the improvement of the actual established standards, due the find results during several audits realized at certificated organizations and at accredited organizations, shown and discussed through this work. This work evaluates the deficiency verified and proposes as guidelines, improvement opportunities, in complement to the methodology established on the ISO 19011:2002 standard. On the author s proposal, although the problem has been delimited to the quality management system audits is also applicable to the others management systems. Concludes, introducing the main aspects to the contribution for the research. Finally, other proposals shall be suggested directing to complement this subject, once this present paper doesn t exhaust the subject.